Situation Report: Bulgaria, 4 September 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Podgorny to Head Soviet Delegation to September 9 Celebrations On the Eve of September 9: Publicity Apparatus in Full Swing The 30th Anniversary of the Outbreak of World War II Bulgaria and the Slovak National Uprising Agreements Signed International Symposia